MANAGEMENT EVENT PROGRAM PARENTING MENGENAI PENGGUNAAN GADGET DAN INERNET BAGI ANAK-ANAK DI SD MUTIARA BUNDA - Pratama, Abisha Akmal; Hafiar, Hanny; Prastowo, FX. Ari Agung (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2017)
Many parents are still unaware of the dangers of the internet and gadgets forchildren. Problems such as sore eyes, nerve damage, change of posture, as well asfatigue due to due to playing the gadget for too long are the hidden dangers of the useof the gadgets and the internet. Views that display adult content such as violence, drugs,pornography, to the LGBT behavior can be seen by the children. The impact of that cancause mental retardation, early maturing, to violence or undue behavior committed bychildren. Based on these phenomena, Mutiara Bunda school conducts a parentingprogram about the dangers of the internet and gadgets for children. Parenting programis an educational program outside the classroom that requires cooperation between theschool and the parents. Parenting programs are based on the fact that children spendmore time at home than in school, therefore parents need to get the educational valuesof the parenting program. In this case is related to the use of gadgets and the internetare unhealthy for children. Parenting program is a good form of cooperation betweenthe school and parents in producing children who are intelligent and virtuous as thefuture generation.